Robust tracking for functional electrical stimulation cycling with unknown time-varying input delays: A switched systems approach - Tong, Xianfang; Zhu, Yanzheng (Frontiers in Neurorobotics, 2022)
Motorized function electrical stimulation (FES) cycling has been demonstrated that it offers multitudinous health benefits for an individual suffered from a neurological disorder. FES-cycling is usually designed to track the desired trajectories in real time. However, there exist input delays between the exertion of the stimulation and the corresponding muscle contraction that potentially destabilizes the system and debases the training efforts. Meanwhile, muscle fatigue gives rise to a time-varying input delay and decreased force. Moreover, switching between FES and motor control can be chattering and destabilizing owing to the high frequency. This article constructs the Lyapunov-Krasovskii functionals to analyse the stability and robustness of the nonlinear cycling system with time-varying input delay. Then, a new average dwell time condition is provided to ensure the input-to-state stability of considered systems. Finally, numerical simulations are illustrated to verify the effectiveness of the developed controller.